Cell type‐specific mechanisms coupling protease‐activated receptor‐1 to infectious colitis pathogenesis. (11th October 2019) - Boucher, Alexander A.; Rosenfeldt, Leah; Mureb, Duaa; Shafer, Jessica; Sharma, Bal Krishan; Lane, Adam; Crowther, Rebecca R.; McKell, Melanie C.; Whitt, Jordan; Alenghat, Theresa; Qualls, Joseph; Antoniak, Silvio; et al.
Abstract: Background: Protease‐activated receptor‐1 (PAR‐1) plays a major role in multiple disease processes, including colitis. Understanding the mechanisms coupling PAR‐1 to disease pathogenesis is complicated by the fact that PAR‐1 is broadly expressed across multiple cell types. Objective: Determine the specific contributions of PAR‐1 expressed by macrophages and colonic enterocytes to infectious colitis. Methods: Mice carrying a conditional PAR‐1 allele were generated and bred to mice expressing Cre recombinase in a myeloid‐ (PAR‐1 ΔM ) or enterocyte‐specific (PAR‐1 ΔEPI ) fashion. Citrobacter rodentium colitis pathogenesis was analyzed in mice with global PAR‐1 deletion (PAR‐1 −/− ) and cell type‐specific deletions. Results: Constitutive deletion of PAR‐1 had no significant impact on weight loss, crypt hypertrophy, crypt abscess formation, or leukocyte infiltration in Citrobacter colitis. However, colonic shortening was significantly blunted in infected PAR‐1 −/− mice, and these animals exhibited decreased local levels of IL‐1β, IL‐22, IL‐6, and IL‐17A. In contrast, infected PAR‐1 ΔM mice lost less weight and had fewer crypt abscesses relative to controls. PAR‐1 ΔM mice had diminished CD3+ T cell infiltration into colonic tissue, but macrophage and CD4+ T cell infiltration were similar to controls. Also contrasting results in global knockouts, PAR‐1 ΔM mice exhibited lower levels of IL‐1β, but not Th17‐related cytokines (ie, IL‐22, IL‐6, IL‐17A). Infected PAR‐1 ΔEPI mice exhibited increased crypt hypertrophy and crypt abscess formation, but local cytokine elaboration was similar to controls. Conclusions: These studies reveal complex, cell type‐specific roles for PAR‐1 in modulating the immune response to Citrobacter colitis that are not readily apparent in analyses limited to mice with global PAR‐1 deficiency.